Relevant aspects of the intercepting of telephone communications in the Spanish criminal process - Varona Jiménez, Alberto (2020)
In these lines, we will analyze the most relevant aspects of the regulation of wiretapping in the Spanish procedural system. The current regulation, product of a reform operated in 2015, incorporates a copious jurisprudence and it responds to the need to safeguard the democratic quality of our procedural system through an adequate respect for the principle of legality. The reform, which incorporated other technological investigation measures, contains relevant aspects such as the objective and subjective scope, the content of the judicial resolution or the definition of the guiding principles for the adoption of the measure.